Comparative study of solar air heater (SAH) roughened with transverse ribs of NACA 0020 in forward and reverse direction. (June 2022) - Kumar, Sanjeev; Das, Randip Kumar; Kulkarni, Kishor
Abstract: Experimental and Numerical investigation of heat transfer and fluid flow characteristics is carried out for SAH duct (aspect ratio, W/H = 10:1) with transverse ribs of different cross-sections (square, semi-circular and symmetric half NACA 0020 in both forward and reverse orientations) on one of its broad wall. Solutions are obtained using SIMPLE algorithm for coupling of pressure and velocity, while for discretization of momentum and energy equations upwind scheme of second order is used in commercial ANSYS software. Nusselt number ( Nu ) and friction factor (f) are evaluated for Reynolds number (Re) ranging from 6000 to 18000, fixed relative roughness pitch (P/e = 12) and relative roughness height (e/D = 0.05). The highest value of ( Nu ) is found for ribs of semi-circular cross-section while minimum (f) is observed for forward oriented symmetric half NACA 0020. The highest thermo-hydraulic performance parameter is achieved at Re = 6000 with symmetric half NACA 0020 rib roughness when used in reverse orientation. Contours plots of temperature, velocity streamlines and pressure variation yielded important results for understanding the physical phenomenon inside the SAH. The numerical outcomes are validated with experimental results.